PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KUALITAS PELAYANAN PENDIDIKAN DI SMP NEGERI 2 MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - MAMAHIT, KLARITA PRISILIA; LENGKONG, FLORENCE DAICY; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2019)
This research aims to find out: is there a principal leadership influence to the quality ofeducational services in the State Junior 2 East Bolaang Mongondow Regency Modayag. This research isquantitative research. The sample in this study are students of SMP Negeri 2 Modayag a numbering 97people. Data collection instruments in the form of a questionnaire, consisting of 8 questions aboutprincipal and 8 questions about the quality of educational services. The issue that you want to answer inthis study which is about whether the leadership of the principal influence on the quality of educationalservices. From the research that has been done and the result of pengolaan data with SPSS. In a test ofthe validity of the shows that all statements on the koesioner there is a valid data because all thecoefficients r count greater than r 0.202 table. Thus, all of the items now declared valid so it can be usedas a research instrument. So also with the reliability test in this research show that the value of thevariable alpha cronbach's the leadership of the principal and the service quality of higher education from0202 then data from the principal and leadership variables the quality of educational services is a datareabel status. If in the view of the t-test because the value t htung of 8.049 > t 1.986 table so that it can beconcluded that there was a great influence on the leadership of the principal (X) to the quality ofeducational services (Y). Based on the hypothesis test showed that there was significant influence betweenthe leadership of the headmaster to quality educational services. This is evidenced showed significantlevels of less than 0.05 0.00 only. It means Ho denied and Ha is received. Based on data obtained from theresults of research done then can be drawn the conclusion that the leadership of the principal influenceon the quality of educational services. Suggestions for teachers and principals in order to provide a serviceand follow the norms of learning with high discipline, thus the process of educational services willproduce a quality learner.Keywords : Leadership, Principal, Service Quality, Education.